ANALISIS PENGGUNAAN POLA PENGEMBANGAN PERKEBUNAN KARET PADA PETANI DI KECAMATAN KUANTAN HILIR - Dewi Novita Sari; Hainim Kadir; Rahmita Budiartiningsih (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in Kuantan Hilir district. The election of this area on the basis that most of the population Kuantan Hilir regency eyed quest in the plantation sector. This study took place in April 2015 until the month of May 2015. The purpose of this study are: to analysis the pattern of development of rubber plantation to farmers in Downstream Kuantan district. The method used in this research is descriptive analysis and qualitative analysis. Data has been obtained are gathered, in the tabulation, and analysis using statistical analysis of non parametik. To complete this study, the authors used primary data obtained from questionnaires that ask authors to respondents, include land owned, type of rubber, the produced and income. as well as secondary data obtained from the goverment agencies Kuantan Singingi and Office Kuantan Hilir. The results of this study indicate that Downstream Kuantan farmers currently use Ex SRDP pattern and self organize pattern. Then the average income of farmes Ex SRDP pattern Rp53.793.000 respondents/year and the average income of farmers self organize pattern Rp53.393.000 respondents/year. The results obtained by T test that production and income farmers pattern Ex SRDP and self organize Since t count smaller than t table is Ex SRDP pattern to (0,5<1,665), and t count self organize pattern (1< 1,992) t table for 95% confidence level. It can be concluded immediately null hypothesis (Ho)is accepted and the hypothesis (Hi) is rejected, so that production and revenues of the farmers Ex SRDP and self organize there is no real difference.Keywords : Ex SRDP Pattern, Self Organize Pattern, Income, and Production.